PENGARUH UKURAN PERUSAHAAN KLIEN, KESULITAN KEUANGAN, UKURAN KAP DAN PERGANTIAN MANAJEMEN TERHADAP AUDITOR SWITCHING (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2013-2015) - Harisman Harisman; Yesi Mutia Basri; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This studied examines the effect of client firm size, financial condition, KAP size and management change on auditor switching. The sample of this study is 32 of manufacturing companies that listed in Bursa Efek Indonesia period 2013-2015. Analytical techniques used to perform the hypothesis testing is purposive sampling method with secondary data and the method of collected data is documentation method. The data got from website www.idx.com. Data are analyzed using logistic regression method using SPSS (Statistical Product and Service Solution) 17 version. The results showed all the variable independent had effect on auditor switching, with nagelkerke r square value 0,423 or 42,3%. The first variable independent firm size client had effect on auditor switching with significance value of 0.021 and H1 accepted, the second variable independent financial distress had effect on auditor switching with significance value of 0.016 and H2 accepted, the third variable independent KAP size had effect on auditor switching with significance value of 0.009 and H3 accepted and the last variable independent management change had effect on auditor switching with significance value of 0.016 and H4 accepted.Keyword : client firm size, financial distress, kap size, management change, auditor switching.